Hadis Anas bin Malik tentang Kesehatan: Studi Takhrij dan Syarah Hadis - Muhammad Taufiq Murtadha; Susanti Vera; Muliadi (Gunung Djati Conference Series, 2022)
The purpose of this study is to discuss the hadith of Anas bin Malik regarding the time limit for shaving or cutting pubic hair, armpit hair, mustache, and nails. This study uses a qualitative approach that emphasizes the study of literature through the takhrij and syarah hadith methods with contemporary analysis. The results of this study found that the quality status of Anas bin Malik's hadith was considered authentic based on the takhrij hadith. And the narration of the hadith shows that the mention of forty days does not encourage us to cut or shave things that have been mentioned once for forty days. However, it does put a limit on how long the hair and nails on the body should be cleaned. This study concludes that the hadith of Anas bin Malik is maqbul (accepted) and of course ma'mul (to be practiced). This study recommends to the whole community, especially Muslims, to maintain cleanliness, especially personal hygiene by practicing the sunnahs of fitrah.